Learning art history and history through Old Batavia’s photos - Iwan Zahar (2012)
Art education has moved towards a more inquiry-based approach to teaching, learning, and thingking about art. The history of art provides a number of diverse modes of inquiry that offer art educatiors new ways of thingking about, looking at, and analysing visual art. Learning history or art history are still problems, and many lecturers focus on the old structure of art history using themes, biographies, and chronologies. Many lecturers focus on remembering names, dates, and time periods; or disseminating oversimplified versions of expert knowledge. In other words, many lecturers still use rotary learning and teacher centre. Choosing artefact, photos, paintings, documentaries file, cataloque raisonne for art history’s materials are one of lecturer’s task; however, those materials are not necessary related to art history. The objective of this paper is to learn art history and history through old photographs, and select old photos for art instruction. Old photos can come from old families photos, royal families portraits, and also topographic bureau. Using old batavia photos, I will discuss the types of photos will suitable for art instructions which shows the art history and history, and to explore three art history inquiry process such as iconology, iconography, and social art history. The study can be concluded that the batavia book can be used as art historical materials.